Revenge Bedtime Procrastination: A Self-Love Phenomenon or Revenge Against Yourself? - Alqo'idah, Wardah; Nabila, Tsania Zahrotun; Ar-raza, Muhammad Firdaus; Supradewi, Ratna (Universitas Muria Kudus, 2023)
Having a hectic daily routine often makes a person lose time to relax for himself, commonly called